Optimizing enzymatic dyeing of wool and leather - Barros, Alexandre António Antunes (2019)
Wool and Leather have been dyed with “in situ” generated pigment by means of laccase-catalysed oxidative coupling of dye precursor ABTS and dye modifier Resorcinol in a batchwise process. The process reaction variables (laccase, precursor and modifier concentrations, temperature and dyeing time) were optimized for wool biocolouration. The temperature, precursor concentration, interaction between precursor and modifier, and time are the most important factors in the dyeing process. The best-optimized wool dying conditions (2h reaction time, 50μl laccase, 500mM mediator, 10mM precursor at 40ºC) were then successfully applied onto leather material. The enzymatic-dyeing optimized process can be successfully performed on wool and leather at low temperature and mild pH obtaining different hues and depths of shades by varying the modifier concentration and time. Moreover, the enzymatic-dye bath solution can be reused several times, which has a huge advantage in terms of cost reduction.